Estudios sobre el África romana : culturas e imaginarios en transformación - Salcedo, Fabiola; Lázaro, Estefaniá Benito; España-Chamorro, Sergio (Archaeopress Publishing Ltd, 2018)
These collected papers are for those who have their gaze fixed on the fascinating mosaic of cultures that was the North-African world from the moment Rome appeared in the region. Most articles are dedicated to the world of images, but other subjects include Historiography, Archaeology of Architecture, and Libyan-Berber ethnicities.
Previously issued in print: 2018.
Available through Archaeopress Digital Subscription Service.
Keywords: Africa, North -- History -- To 647.; Africa, North -- Antiquities, Roman.; Africa, North -- Civilization.; Berbers -- Africa, North -- Social life and customs.; Afrique du Nord -- Histoire -- Jusqu'à 647.; Afrique du Nord -- Antiquités romaines.; Berbères -- Afrique du Nord -- Mœurs et coutumes.; SOCIAL SCIENCE / Archaeology; Berbers -- Social life and customs; Civilization; Classical antiquities; North Africa; Berber; Kulturkontakt; Römer; Africa; Africa (region); To 647; History